Circadian rhythms in liver metabolism and disease - Jessica M. Ferrell; John Y.L. Chiang (Elsevier, 2015)
Mounting research evidence demonstrates a significant negative impact of circadian disruption on human health. Shift work, chronic jet lag and sleep disturbances are associated with increased incidence of metabolic syndrome, and consequently result in obesity, type 2 diabetes and dyslipidemia. Here, these associations are reviewed with respect to liver metabolism and disease.